Selective recognition of fluoride and acetate by a newly designed ruthenium framework: experimental and theoretical investigations - Kundu, Tanaya; Chowdhury, Abhishek Dutta; De, Dipanwita; Mobin, Shaikh M.; Puranik, Vedavati G.; Datta, Anindya; Lahiri, Goutam Kumar (Dalton Transactions, 2012)
{An effective anion sensor, [Ru-II(bpy)(2)(H2L-)](+) (1(+)), based on a redox and photoactive {Ru-II(bpy)(2)} moiety and a new ligand (H3L = 5-(1H-benzo[d]imidazol-2-yl)-1H-imidazole-4-carboxylic acid), has been developed for selective recognition of fluoride (F-) and acetate (OAc-) ions. Crystal structures of the free ligand, H3L and [1](ClO4) reveal the existence of strong intramolecular and intermolecular hydrogen bonding interactions. The structure of [1](ClO4) shows that the benzimidazole N-H of H2L- is hydrogen bonded with the pendant carboxylate oxygen while the imidazole N-H remains free for possible hydrogen bonding interaction with the anions. The potential anion sensing features of 1(+) have been studied by different experimental and theoretical (DFT) investigations using a wide variety of anions, such as F-, Cl-, Br-, I-, HSO4-, H2PO4-, OAc- and SCN-. Cyclic voltammetry and differential pulse voltammetry established that 1(+) is an excellent electrochemical sensor for the selective recognition kof F- and OAc- anions. 1(+) is also found to be a selective colorimetric sensor for F- or OAc- anions where the MLCT band of the receptor at 498 nm is red shifted to 538 nm in the presence of one equivalent of F- or OAc- with a distinct change in colour from reddish-orange to pink. The binding constant between 1(+) and F- or OAc- has been determined to be logK = 7.61 or 7.88, respectively, based on spectrophotometric titration in CH3CN. The quenching of the emission band of 1(+) at 716 nm (lambda(ex) = 440 nm